A sourcebook of feminist theatre and performance : on and beyond the stage - Martin, Carol, 1952- (Worlds of performance., 1996)
This outstanding collection includes key texts by theorists such as Elin Diamond, Peggy Phelan and Lynda Hart and interviews with practitioners including Anna Deavere Smith and Robbie McCauley.